ინდოეთისა და პაკისტანის სახელმწიფო მოღვაწეებთან ქართველთა ურთიერთობის ისტორიიდან (XX საუკუნის 50-70-იანი წლები) - ჯავახიშვილი, ნიკო (მერიდიანი, 2012)
This paper covers the relationship between the statesmen of India and Pakistan and the prominent representatives of the Georgian emigre circles like General Shalva Maghlakelidze (1894-1976) and Mikheil Kavtaradze (1906- 2008), member of the Georgian National-Democratic party and pamphleteer, as well as Alexandre Chikvaidze (born 1933), the ethnic Georgian USSR diplomat, and Iliko Sukhishvili (1907-1985) and Nino Ramishvili (1910-2000), the famed choreographers, founders and leaders of the Georgian National Ballet.
ON THE HISTORY OF GEORGIANS’ RELATIONSHIP WITH STATESMEN OF INDIA AND PAKISTAN (IN THE 1950s-1970s)
https://geohistory.humanities.tsu.ge/ge/procedings/83-shromebi/146-shromebi-5.html
Keywords: ინდოეთი; პაკისტანი; საქართველო; საერთაშორისო ურთიერთობები